Effect of Postsowing Compaction on Cold and Frost Tolerance of North China Plain Winter Wheat. (13th March 2017) - Lu, Caiyun; Zhao, Chunjiang; Wang, Xiu; Meng, Zhijun; Song, Jian; McGiffen, Milt; Wu, Guangwei; Fu, Weiqing; Dong, Jianjun; Yu, Jiayang
Abstract : Improper postsowing compaction negatively affects soil temperature and thereby cold and frost tolerance, particularly in extreme cold weather. In North China Plain, the temperature falls to 5 degrees below zero, even lower in winter, which is period for winter wheat growing. Thus improving temperature to promote wheat growth is important in this area. A field experiment from 2013 to 2016 was conducted to evaluate effects of postsowing compaction on soil temperature and plant population of wheat at different stages during wintering period. The effect of three postsowing compaction methods—(1) compacting wheel (CW), (2) crosskill roller (CR), and (3) V-shaped compacting roller after crosskill roller (VCRCR)—on winter soil temperatures and relation to wheat shoot growth parameters were measured. Results showed that the highest soil midwinter temperature was in the CW treatment. In the 20 cm and 40 cm soil layer, soil temperatures were ranked in the following order of CW > VCRCR > CR. Shoot numbers under CW, CR, and VCRCR treatments were statistically 12.40% and 8.18% higher under CW treatment compared to CR or VCRCR treatments at the end of wintering period. The higher soil temperature under CW treatment resulted in higher shoot number at the end of wintering period, apparently due to reduced shoot death by cold and frost damage.